French Laïcité and Freedom of Conscience - Tsereteli, Nikoloz (Journal of Law, 2025)
The proper regulation of the political and legal relationship between church and state constitutes one of the most important challenges for states. In accordance with the historical development of civil society, states at different times have sought to devise forms of governance in which the institution of the church would also be represented in its own way. In this regard, one distinctive secular form of such relations is French Laïcité. Accordingly, the present paper examines the history of the origin of this model and the dynamics of its development. Particular attention is paid to its role in the formation of a modern democratic and legal system of governance and, ultimately, to the peaceful coexistence of church and state.